DRAM1 enhances the proliferation and metastasis of gastric cancer through the PI3K/AKT/mTOR signaling pathway and energy metabolism - Xinrong Wu; Yifan Li; Weiwei Wang; Jiale Xu; Bei Zhao; Wenqi Sun; Dan Ge; Longying Xiong; Xiaotan Dou; Xiaoping Zou; Lei Wang; Min Chen (Scientific Reports)
Abstract Gastric cancer (GC) is a prevalent malignant tumor of the digestive system that is often diagnosed at advanced stages owing to inconspicuous early symptoms and a lack of specific examination methods. Effective treatment of advanced stages remains challenging, emphasizing the need for new therapeutic targets. Metabolic reprogramming, a hallmark of tumors, plays a pivotal role in tumor progression, immune evasion, and immune surveillance. DNA damage-regulated autophagy modulator 1 (DRAM1) encodes a hexameric transmembrane protein that is predominantly located in lysosomes and induces autophagy; however, its mechanism of action in gastric cancer remains unclear. Our study found that elevated DRAM1 expression in patients with GC correlated with survival and prognosis. DRAM1 knockdown suppressed energy metabolism in GC cells through the PI3K/AKT/mTOR signaling pathway, thereby mitigating GC progression. Atorvastatin, a focus of recent tumor research, significantly enhanced apoptosis levels in DRAM1 knockdown GC cells compared to the control group. Therefore, through metabolic reprogramming, DRAM1 may serve as a potential therapeutic target for GC prevention.